“There and back again” - Ultrastructural changes in the gills of Bathymodiolus vent-mussels during symbiont loss: Back to a regular filter-feeding epidermis - Piquet, Bérénice; Le Panse, Sophie; Lallier, François H.; Duperron, Sébastien; Andersen, Ann C. (Frontiers in Marine Science, 2022)
Deep-sea mussels Bathymodiolus azoricus, from Azorean hydrothermal vents, house two types of symbionts in their fleshy gills: methane-oxidizing (MOX) and sulfide-oxidizing (SOX) Gamma-proteobacteria. As soon as the mussels are collected, their symbionts are deprived from their environmental nutrient flux, and cannot rely on their usual metabolism. Recent studies have shown that the gill cells undergo high rates of apoptosis, as well as regionalized cell proliferation. This study follows the fate of the symbionts and of the hosting bacteriocytes at the ultrastructural level, during an extended starvation period. Just upon collection, we evidenced an apico-basal journey of the symbionts in the bacteriocytes, starting with (1) apical single symbiont endocytosis, (2) symbiont division, (3) symbiont storage, (4) and symbiont digestion within lysosomes, above the basal lamina. After 4-9 days starvation, endocytosis occurred with (5) empty blebbing, (6) the lysosomes increased in size, and the bacteriocytes lost their apical membrane, resulting in a (7) baso-apical return of the symbiont-containing lysosomes outside the gills, while the nucleus showed condensed chromatin, characteristic of apoptosis/necroptosis (8). Between the bacteriocytes, narrow intercalary cells appear to divide (9). Our hypothesis is that intercalary cells are stem cells that replace lost bacteriocytes. After 61 days there was no symbiont left, and the epidermis resembled those of the non-symbiotic filter-feeding mussel Mytilus edulis.